Creative Economy Event Model in Improving the Economy in the Village - Tutik, Tutik; Mistriani, Nina; Solichoel, Solichoel (Budapest International Research and Critics University, 2022)
This study aims to find out how to increase people's income by utilizing the wealth of the village's creative economy, especially through cultural events. The purpose of tourism development research can be carried out through improving the creative economy of the community in cultural events with collaboration through human resources, relief, community products, as well as promotion through various media and planned in the event calendar. This research was conducted in Branjang Village, Semarang Regency, Central Java Province. This research is important to determine the potential of the creative economy which is the strength of Branjang Village to support tourism development. With cultural events, it indirectly has an impact on the surrounding community to create and promote creative products that can be marketed during the event. Cultural events are held indirectly to become an interesting promotional medium, because in addition to displaying various existing cultural uniqueness, it also displays various arts, culinary, crafts, natural wealth, interesting spots in the village and of course creative economy products. So that with an attractive packaging, it will give an impression to potential visitors. Cultural Event activities can improve the community's economy and the more pariwiata events are carried out, the more interest in visiting again increases, especially tourists so that they want to come back and visit the village. The visit will certainly provide enthusiasm for the community to continue to provide natural wealth and the various creative economies they have, so that the surrounding community will also benefit from the development of tourism. This research was conducted using qualitative methods using various sources including regional tourism offices, village officials, village managers, tourism managers, business actors, local communities and tourists. The output targeted in this study is published in 3 accredited journal articles in the Scientific Journal of Management and Business.